Antecedents of work engagement among high potential employees. Issue 5 (12th September 2016) - Khoreva, Violetta; van Zalk, Maarten
Abstract : Purpose: The implicit assumption since the beginning of the science and practice of human resource management (HRM) has been that if we do HRM well, this will somehow make organizations perform more effectively. The purpose of this paper is to address this "somehow" by investigating the antecedents of work engagement among high potential employees. Design/methodology/approach: The data were collected through a web-based survey from 439 high potential employees of 11 Finnish multinational enterprises. Structural equation modeling was utilized to analyze the data. Findings: In line with the social exchange perspective, the findings demonstrate that it is through the fulfillment of psychological contract and through increased organizational identification that high potential employees become more engaged with their organizations in response to participation in leadership development activities. Research limitations/implications: Given its cross-sectional nature, the authors cannot completely exclude the possibility of common method bias having impact on the study results. The authors thus call for longitudinal research to examine the nature of causality within the associations analyzed in this study. Originality/value: This is one of the first empirical studies, which examines the previously underexplored association between leadership development activities and employee attitudes. In addition, this study addresses the lack of research investigating such a specific group of employees as high potential employees, those employees who rank at the top in terms of performance and competencies, and who are considered to be of highest concern for organizations.